Integrating Islamic Teachings: Enhancing Environmental Awareness in the Digital Era Through Qur'anic Interpretations - Muhriningsih, Vivin Tri; Shofa, ⁠Ida Kurnia; Gifari, Muhammad (Program Studi Ilmu Al-Qur'an dan Tafsir Fakultas Ushuluddin dan Filsafat, UIN Ar-Raniry, 2024)
This study aims to explore the contributions of classical and contemporary Qur'anic interpretations to environmental ethics and to evaluate their relevance and application in the context of modern environmental challenges. Employing a qualitative analysis, the study reviews key interpretations from eminent scholars such as Imam Ar-Razi, Al-Maraghi, and M. Quraish Shihab. The analysis is grounded in their exegeses of specific Qur'anic verses related to environmental stewardship, integrating both classical and contemporary perspectives. The interpretations collectively underscore the Qur'anic advocacy for an integrated approach to environmental care, emphasizing balance, justice, and the moral implications of human interactions with the environment. Imam Ar-Razi's interpretations highlight the spiritual causation of environmental harm, while Al-Maraghi and Shihab focus on the principles of balance and justice as central to ecological stewardship. The study reaffirms that Qur'anic teachings provide a profound ethical framework for addressing the environmental crisis, advocating for a holistic approach that incorporates spiritual, moral, and practical dimensions. These findings suggest the need for greater integration of religious teachings in environmental education and policy-making. Promoting a deeper understanding of ecological ethics among religious communities could foster more sustainable environmental practices.